Mesenchymal Stem Cells as a Biological Drug for Heart Disease. Issue 3 (17th July 2015) - Sanina, Cristina; Hare, Joshua M.
<x xml:space="preserve">Abstract</x> Cell-based treatment represents a new generation in the evolution of biological therapeutics. A prototypic cell-based therapy, the mesenchymal stem cell, has successfully entered phase III pivotal trials for heart failure, signifying adequate enabling safety and efficacy data from phase I and II trials. Successful phase III trials can lead to approval of a new biological therapy for regenerative medicine.